2002
DOI: 10.5012/bkcs.2002.23.12.1790
|View full text |Cite
|
Sign up to set email alerts
|

The Coordination Chemistry of DNA Nucleosides on Gold Nanoparticles as a Probe by SERS

Abstract: The DNA nucleosides (dA, dC, dG, dT) bound to gold nanoparticles (~13 nm) in aqueous solution has been studied as a probe by the SERS and their coordination structures have been proposed on the basis of them. According to UV-Visible absorption of gold nanoparticles after modifying with DNA nucleosides, the rates of absorption of dA, dC, and dG were much faster than that of dT as monitored by the aggregation kinetics at 700 nm. These data indicated that the nucleosides dA, dC, and dG had a higher affinity for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(32 citation statements)
references
References 44 publications
3
28
1
Order By: Relevance
“…The LODs are dependent not only on the plasmonic efficiency of the substrate but also on the binding affinity of the chemical to that substrate. Several studies examining the binding of nitrogen-containing compounds to different metals, including Ag and Au, have been conducted. Acioli and Srinivas studied nucleobase binding to Ag and Au. The authors found that (i) both Ag and Au bind the nucleobases through a nitrogen site and (ii) an Au surface had twice the binding energy of an Ag surface.…”
Section: Resultsmentioning
confidence: 99%
“…The LODs are dependent not only on the plasmonic efficiency of the substrate but also on the binding affinity of the chemical to that substrate. Several studies examining the binding of nitrogen-containing compounds to different metals, including Ag and Au, have been conducted. Acioli and Srinivas studied nucleobase binding to Ag and Au. The authors found that (i) both Ag and Au bind the nucleobases through a nitrogen site and (ii) an Au surface had twice the binding energy of an Ag surface.…”
Section: Resultsmentioning
confidence: 99%
“…For the band assignment the spectral features were compared with those of SERS and Raman spectra of adenine derivates (deoxyadenosine (dA) [27], deoxyadenosine monophosphate (AMP) [28] and single stranded adenine homopolymer (poly(dA)) [29]).…”
Section: Resultsmentioning
confidence: 99%
“…An example is the band at 1251 cm −1 in spectrum 3. It can be attributed to the (C 8 –H, N 9 –H) deformation, the (N 7 –C 8 ) stretching of adenine [35], a ring mode of adenine or cytosine [37], the (C 8 –N 9 ) stretching of guanine [27] or the in-plane ring stretching of thymine [35]. …”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] The DNA nucleosides bound to gold nanoparticles in aqueous solution were studied with surface-enhanced Raman scattering. 13 The temperatureprogrammed desorption experiments show that the heat of desorption of DNA bases from gold thin film decreases in the order of G > A > C > T. 8 The base-dependent competitive adsorption of single-stranded DNA on polycrystalline Au films indicates that the adsorption affinity to gold surface decreases in the order of A > C ≥ G > T. 14 On the other hand, the isothermal titration calorimetry studies on the binding of DNA bases to gold nanoparticles show that the strength of nucleobase-gold interaction decreases in the a) Author to whom correspondence should be addressed. Electronic mail: zhengwj@iccas.ac.cn.…”
Section: Introductionmentioning
confidence: 99%